Cyber Infidelity sebagai Dasar Perceraian Perspektif Hukum Islam dan Hukum Positif Indonesia - Sadam (Qonuni: Jurnal Hukum dan Pengkajian Islam, 2025)
The development of digital technology has transformed patterns of communication and interpersonal relationships within family life, including the emergence of cyber infidelity, which is increasingly used as grounds for divorce in Indonesia. This phenomenon raises new legal issues regarding the position of virtual infidelity within Islamic family law and Indonesian positive law, as well as the use of electronic evidence in judicial proceedings. This study aims to analyze the forms of cyber infidelity, the legal standing of electronic evidence in divorce cases, and its implications for household harmony and the development of digital family law in Indonesia. The research employed a qualitative approach using a normative juridical design combined with a socio-legal approach. Data were collected through documentation studies of Religious Court decisions from 2023–2025, statutory regulations, and relevant scientific literature. Data analysis was conducted using an interactive analysis model consisting of data reduction, data presentation, and systematic conclusion drawing. The findings reveal that the most dominant forms of cyber infidelity include romantic communication through social media and instant messaging applications, virtual sexual relationships, the use of online dating applications, and hidden emotional relationships with third parties. Electronic evidence such as chat screenshots, social media activity records, and digital documents plays an important role in divorce proceedings, although its implementation still faces challenges related to authenticity and the absence of uniform evidentiary standards. This study concludes that the development of digital technology has influenced concepts of fidelity, family dynamics, and family law evidentiary systems, thereby requiring the development of family law regulations that are more adaptive to the digital transformation of modern society.